Efeitos da inibição da síntese de óxido nítrico e da suplementação de L-arginina na hipertrofia muscular esquelética - Santos, Jean Carlos Loura dos (2019)
In recent years, the number of nitric oxide (NO) supplements has increased. Even indirectly, it is not known whether NO participates in the modulation of skeletal muscle hypertrophy. Few studies suggest that NO is important in the process of skeletal muscle hypertrophy. NO supplementation may lead to greater vasodilation in the stimulated muscles, which allows for greater blood supply and increased amino acid intake for protein synthesis. The purpose of this study was to investigate whether inhibition of NO synthesis through NG-nitro-L-arginine methyl ester (L-NAME) and L-arginine supplementation are able to modulate skeletal muscle hypertrophy. Wistar rats (n = 56), body weight between 200-250g, were randomly allocated into ten (10) experimental groups: 7 days non-ablation control (C7), 7 days ablation control (CA7), 7 days ablation L-NAME (LN7), 7 days non-ablation L-NAME (LNA7), 7 days Larginine non-ablation (LA7), 7 days L-arginine ablation (LAA7), 21 days control non-ablation (C21), 21 days control ablation (CA21), 21 days L-arginine non-ablation (LA21) and 21 days L-arginine ablation (LAA21). Two (2) groups treated with L-NAME (LN21 and LNA21) were excluded from the study due to the high mortality rate at the time of anesthesia for ablation surgery. The induction of muscle hypertrophy was performed through a synergistic ablation surgical procedure. The soleus was used for post mortem analysis and for crosssectional area (CSA) determination. The statistical program used was Graphpad prism 8, the data were expressed as mean ± standard error of the mean (SEM). The significance level considered for all variables was 5%. Results show that final body weight and body weight gain presented statistically higher values in groups LA21 and LAA21/LA7 and LAA7, respectively. The total weight of the soleus muscle was statistically higher in groups LA21 and LAA21. However, CSA, perimeter and diameter of muscle fibers were similar among groups. In conclusion, L-NAME was not able to promote atrophy after 7 days of administration, however, supplementation with L-arginine for 21 days caused changes in body composition. In addition, L-Arginine supplementation induced hypertrophy after the gastrocnemius muscle tenotomy process, suggesting a better response to L-arginine after longer periods of administration.